2003
DOI: 10.1001/archinte.163.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Is an Inadequate Screening Test for Renal Failure in Elderly Patients

Abstract: Serum creatinine is a poor screening test for renal failure in elderly patients, leading to marked underinvestigation and underrecognition of renal failure in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
0
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(195 citation statements)
references
References 32 publications
14
164
0
11
Order By: Relevance
“…This explains the high inter-individual variability of SCr, which precludes a reliable estimation of kidney function from a single creatinine measurement without additional patient data (12). As a result, SCr has poor sensitivity for renal failure or mild renal dysfunction, particularly in children, malnourished or elderly patients and severely ill patients, with consequent under-recognition of renal impairment (14,15).…”
Section: Creatininementioning
confidence: 99%
“…This explains the high inter-individual variability of SCr, which precludes a reliable estimation of kidney function from a single creatinine measurement without additional patient data (12). As a result, SCr has poor sensitivity for renal failure or mild renal dysfunction, particularly in children, malnourished or elderly patients and severely ill patients, with consequent under-recognition of renal impairment (14,15).…”
Section: Creatininementioning
confidence: 99%
“…A few studies have demonstrated that primary care physicians relying on serum creatinine fail to diagnose CKD in elderly patients, 16,17 and that diagnostic rates can be improved by providing estimated GFR (eGFR) based on either the CG or MDRD equations. [17][18][19] Whether such recognition leads to changes in physician practice which may slow the progression of chronic kidney disease is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The median duration of hospitalization was 15 days (13)(14)(15)(16)(17)(18)(19)(20)(21). Patients who died at baseline had higher values of all biochemical markers, leukocytes and haemoglobin levels.…”
Section: Resultsmentioning
confidence: 99%